Comparative ecology of three species of Thamnodynastes (Serpentes, Dipsadidae) in subtropical-temperate South America - Bellini, Gisela Paola (2014)
Two hypotheses have been proposed to explain the differences among species within present-day communities: the competition-predation hypothesis (CPH) and the deep history hypothesis (DHH). However, the lack of information about the ecology of many species hinders clarification of the role of these different, though not mutually exclusive, hypotheses. We compared ecological data of three species of snakes (genus Thamnodynastes) in their subtropical-temperate geographical distributions, evaluating the reproductive biology, sexual dimorphism, feeding ecology and habitat use of T. hypoconia and T. strigatus, and providing the first ecological data of T. chaquensis. Females attained sexual maturity at larger sizes than males. Unusually for viviparous snakes, males and females had similar body sizes although males had more ventral scales than females. The reproductive cycle of females was seasonal (not annual), with parturition occurring in summer. Males of T. chaquensis and T. strigatus were characterised by continuous reproductive cycles, while males of T. hypoconia showed differences between seasons. All three species mainly fed on amphibians. Thamnodynastes strigatus also fed on fishes, lizards and mammals, T. hypoconia occasionally fed on lizards, while T. chaquensis was an amphibian specialist. Thamnodynastes hypoconia lived in lentic aquatic habitats, T. strigatus was the most aquatic species, and T. chaquensis was the most terrestrial species. We propose that most of the ecological traits examined are phylogenetically conservative within the Tachymenini, supporting the DHH.